Pelayanan Airport Representative pada Era New Normal di Hotel Four Seasons Resort Bali at Jimbaran Bay - Ni Ketut Sekarti; Wayan Melano; Putu Gede Eka Darmaputra (Journal of Hospitality Accommodation Management (JHAM), 2022)
The background of this research is the discovery of obstacles that make the services of airport representative officers less than optimal in the new normal era. The goal of this research is to find out the services of airport representative staff in the new normal era which were adapted to the standard operating procedures applicable at the Four Seasons Resort Bali at Jimbaran Bay. Techniques that are used in gathering the required data are interviews and documentations. The results of this research shows that the implementation of standard operating procedures has been going well, but there are obstacles while on duty so it can be concluded that airport representatives at the Four Seasons Resort Bali in Jimbaran Bay experienced problems while on duty, causing services to be less than optimal. Airport representative staff have carried out their duties in accordance with applicable standard operating procedures